Unruptured retroperitoneal pregnancy implanted in the left broad ligament: A case report - Kutlešić, Ranko Miodrag; Lukić, Bojan; Kutlešić, Marija S.; Popović, Jasmina; Stefanović, Milan; Vukomanović, Predrag; Lilić, Goran (Vojnosanitetski pregled, 2017)
Introduction. Retroperitoneal ectopic pregnancy is extremely rare, but potentially fatal condition due to possible massive hemorrhage, representing a great challenge to clinicians. Case report. We presented early retroperitoneal pregnancy in a patient with previous caesarean section, diagnosed at the sixth gestational week, located in the left broad ligament, primary treated by laparoscopy, which had to be converted to laparotomy due to massive intraoperative bleeding from the implantation site. Conclusion. High index of suspicion, combined with carefully interpreted clinical and ultrasound findings are crucial for the timely diagnosis of retroperitoneal pregnancy, before the occurrence of severe bleeding. The rising, even plateau of serum β-human chorionic gonadotropin (β-HCG) levels without identification of uterine or ectopic (tubal) pregnancy should cause suspicion on ectopic pregnancy in unusual location.